Original research: knowledge and attitude for information gathering practices related to COVID-19: a cross sectional study amongst healthcare workers in New Delhi - Malhotra, Anureet; Siwach, Ishaan; Yadav, Geeta (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID cases in India have surpassed the 50,000 mark as per data available on 7th May with more than 1783 reported deaths. Measures have been deployed by competent authorities to optimally educate healthcare workers (HCWs) in various aspects of this novel disease. Along with an assessment of the prevailing knowledge regarding COVID among HCWs, our study aimed to gather insight into the resources used and efforts made to keep up with the latest developments taking place during the pandemic. Methods: A cross sectional web-based study was conducted in April 2020 using a self-prepared 38 item questionnaire which was distributed to HCWs. Appropriate statistical tools were used for data analysis with p-value < 0.05 being considered as significant. Results: 275 HCWs completed the survey with a response rate of 40.1% with a majority of respondents being doctors (56.6%) and medical students (34.9%). Respondents showed suboptimal knowledge about clinical features, prevention, treatment, and complications of COVID-19. Mean % correct responses were 52.89% (SD+9.83%). Information seeking efforts made by respondents significantly correlated with their knowledge(p=0.043). Official government websites were the most used resource (37.8%). HCWs who had received formal training/guidelines from their institutions had higher knowledge (p=0.003). Conclusions: It is of utmost significance to identify and bridge critical gaps in knowledge by using authentic sources of information to improve understanding of this novel disease to ensure better patient outcomes.